2020
DOI: 10.1111/1467-968x.12197
|View full text |Cite
|
Sign up to set email alerts
|

Routes Towards The Irrealis

Abstract: Irrealis markers are characterized by the rampant heterogeneity of their distributional patterns and by the tendency to appear as portmanteau morphemes encoding other grammatical categories (e.g. person). These and other characteristics may find an explanation in diachronic terms, by taking into account the sources from which irrealis markers derive. In this paper, the most frequent sources of irrealis markers are identified by means of a diachronic-typological survey based on a 100-language sample: these incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…While such typological research has confirmed that the past habitual is cross-linguistically used to express various functions falling under the problematic descriptive header of irrealis, it has also shown that the forms expressing habituality and some irrealis functions display "considerable structural and functional diversity cross-linguistically" (Cristofaro 2004: 261). 6 Since the utility of the descriptive notion of irrealis has met with growing critique (Haan 2012;Sansò 2020), it would appear prudent to move away from such form-functional comparison on a larger scale and focus on the description of specific diachronic paths leading to past habituality. After all, Sansò's (2020: 24) diachronic typological survey of irrealis markers recently concluded that such synchronically multi-functional markers have undergone a long historical process whereby they obtained the different functions that fall under the irrealis label.…”
Section: Cross-linguistic and Historical Connections With Past Habitu...mentioning
confidence: 99%
See 1 more Smart Citation
“…While such typological research has confirmed that the past habitual is cross-linguistically used to express various functions falling under the problematic descriptive header of irrealis, it has also shown that the forms expressing habituality and some irrealis functions display "considerable structural and functional diversity cross-linguistically" (Cristofaro 2004: 261). 6 Since the utility of the descriptive notion of irrealis has met with growing critique (Haan 2012;Sansò 2020), it would appear prudent to move away from such form-functional comparison on a larger scale and focus on the description of specific diachronic paths leading to past habituality. After all, Sansò's (2020: 24) diachronic typological survey of irrealis markers recently concluded that such synchronically multi-functional markers have undergone a long historical process whereby they obtained the different functions that fall under the irrealis label.…”
Section: Cross-linguistic and Historical Connections With Past Habitu...mentioning
confidence: 99%
“…An historical path would perhaps be even of cross-linguistic importance because there are languages which use habitual aspect to express counterfactuals e.g. in Hindi (Karawani 2014: 112), Modern Greek (Mendez Dosuna 2017 or in Ute where it marks future, habitual, future in the past, counterfactual, and other functions (Givón 2011: 134;Sansò 2020). Finally, epistemic certainty also plays a role in the development of the future usage of will, since it passed through a similar pivotal stage where volition is interpreted as proclivity (Ziegeler 2006(Ziegeler , 2013contra Bybee et al 1994: 156-158).…”
Section: Cross-linguistic and Historical Connections With Past Habitu...mentioning
confidence: 99%